Comparison of Benefits Provided by Different Hearing Aid Technologies - Walden, Brian E.; Surr, Rauna K.; Cord, Mary T.; Edwards, Brent; Olson, Laurel (Journal of the American Academy of Audiology, 2000)
The performance of 40 hearing-impaired adults with the GN ReSound digital BZ5 hearing instrument was compared with performance with linear hearing aids with input compression limiting (AGC-I) or two-channel analog wide dynamic range compression (WDRC) instruments. The BZ5 was evaluated with an omnidirectional microphone, dual-microphone directionality, and a noise reduction circuit in combination with dual-microphone directionality. Participants were experienced hearing aid users who were wearing linear AGC-I or analog WDRC instruments at the time of enrolment. Performance was assessed using the Connected Speech Test (CST) presented at several presentation levels and under various conditions of signal degradation and by the Profile of Hearing Aid Benefit (PHAB). Subjective ratings of speech understanding, listening comfort, and sound quality/naturalness were also obtained using 11 -point interval scales. Small performance advantages were observed for WDRC over linear AGC-I, although WDRC did not have to be implemented digitally for these performance advantages to be realized. Substantial performance advantages for the dual microphones over the omnidirectional microphone were observed in the CST results in noise, but participants generally did not perceive these large advantages in everyday listening. The noise reduction circuit provided improved listening comfort but little change in speech understanding.Abbreviations: AGC-I = automatic gain control with input compression limiting, APHAB = Abbreviated Profile of Hearing Aid Benefit, AV = Aversiveness subscale of the PHAB, BN = Background Noise scale of the PHAB, BT2 = behind-the-ear model of GN ReSound analog WDRC hearing aid, BTE = behind-the-ear hearing aid, BZ5 = model name for the trial hearing aid, BZ5DR = directional mode of BZ5, BZ5DR+NR = directional and noise reduction mode of BZ5, BZ5OMNI = omnidirectional mode of BZ5, CD = critical difference, CST = Connected Speech Test, DFS = digital feedback suppression, DS = Distortion Scale of the PHAB, ED3 = in-the-ear model of GN ReSound WDRC analog hearing aid, IC4 = in-the-canal model of GN ReSound WDRC analog hearing aid, LINAGC = linear hearing aid with input compression limiting, NAL-R = National Acoustic Laboratories-Revised, NH = normal hearing, NR = noise reduction, NU-6 = Northwestern University Auditory Test No. 6, PHAB = Profile of Hearing Aid Benefit, PLS = prototype listening situation, QT = Quiet scale of the PHAB, rau = rationalized arcsine unit, RC = Reduced Cues scale of the PHAB, REV = reverberation, S/N = signal-to-noise ratio, UA = unaided, WDRC = wide dynamic range compression, WDRCANLG = analog version of WDRC hearing aid
Keywords: Benefit; digital; directionality; dual microphones; GN ReSound BZ5 hearing instrument; hearing aids; linear; noise reduction; wide dynamic range compression